2004
DOI: 10.2307/4149020
|View full text |Cite
|
Sign up to set email alerts
|

Imagination or Exposure Causes Imagination Inflation

Abstract: To examine the effects of exposure to complex autobiographical events on imagination inflation, subjects performed a 3-stage procedure. First, they rated their confidence that a list of events had happened in their childhood. Second, subjects imagined and paraphrased complex fictitious events 0, 1, 3, or 5 times. Finally, they rated their confidence for the childhood events a second time. We found that subjects became more confident that the fictitious events really did happen in childhood, regardless of wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…Wegner, Schneider, Carter, & White, 1987). Research has demonstrated that exposing people to false information through a range of techniques that encourage them to spend time processing this information-such as imagining false events or explaining how they might have happenedmakes them more confident that the false information was true (Bernstein, Whittlesea, & Loftus, 2002;Sharman, Garry, & Beuke, 2004;Sharman, Manning, & Garry, 2005). In the current experiment, it is possible that exposing people to the misleading information in closed specific question structures should also encourage them to spend time processing this information.…”
mentioning
confidence: 90%
“…Wegner, Schneider, Carter, & White, 1987). Research has demonstrated that exposing people to false information through a range of techniques that encourage them to spend time processing this information-such as imagining false events or explaining how they might have happenedmakes them more confident that the false information was true (Bernstein, Whittlesea, & Loftus, 2002;Sharman, Garry, & Beuke, 2004;Sharman, Manning, & Garry, 2005). In the current experiment, it is possible that exposing people to the misleading information in closed specific question structures should also encourage them to spend time processing this information.…”
mentioning
confidence: 90%
“…Although the precise mechanisms responsible for this effect are unclear, Garry and Polaschek (2000) suggested that the act of imagination evokes detailed mental images or increased familiarity that later results in source confusion and increased certainty in event reality. However, more recently simple exposure to an event by solving anagrams (Bernstein, Whittlesea, & Loftus, 2002), paraphrasing (Sharman, Garry, & Beuke, 2004), or even explaining event information without specific imagination has also been demonstrated to induce this 'imagination' inflation effect (Sharman, Manning, & Garry, 2005). Hence, these findings can be more effectively explained using a processing fluency account.…”
mentioning
confidence: 97%
“…Whereas some experimenters have attempted to extend this social contagion paradigm to more ecologically valid stimuli, particularly in the forensic context (e.g., Gabbert et al, 2003), this research has not yet examined emotional, personally experienced autobiographical memories (but for examples of other false memory research see Garry & Gerrie, 2005;Loftus, 2005Loftus, , 1997Sharman, Garry, & Beuke, 2004).…”
Section: Social Contagion Of Memorymentioning
confidence: 99%